2018
DOI: 10.4067/s0717-95022018000100262
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Body Composition and Physiological Characteristics of Active/Inactive Elderly Women

Abstract: RUIZ-MONTERO, P. J. & CASTILLO-RODRÍGUEZ, A.Differences between body composition and physiological characteristics of active/inactive elderly women. Int. J. Morphol., 36(1):262-266, 2018. SUMMARY:Aging affects living organisms and produces a continuous degenerative change in most physiological functions, specifically in body composition. The aim of the present study is to compare the differences of body composition and physiologic characteristics according to physical activity levels and population of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
2
0
4
Order By: Relevance
“…De los 41 artículos, encontramos nueve que emplean el método Pilates para la mejora de la fuerza muscular (Bergamin et al, 2015;Bertoli et al, 2018;Choi et al, 2019;de Carvalho, Mesquita, Pereira, Neto & Amaro Zangaro, 2017;de Oliveira, de Oliveira & Pires-Oliveira, 2018de Oliveira, Pires-Oliveira, Abucarub, de Oliveira & de Oliveira, 2017;Pinheiro et al, 2014); trece para mejorar el equilibrio y disminuir el riesgo de caídas (Aibar-Almazan et al, 2019;Barker et al, 2016;Bird & Fell, 2014;Cruz-Diaz et al, 2015;Gabizon, Press, Volkov, & Melzer, 2016;Irez, 2014;Josephs, Pratt, Calk Meadows, Thurmond, & Wagner, 2016;Markovic, Sarabon, Greblo & Krizanic, 2015;Mesquita, de Carvalho, Freire, Neto & Zangaro, 2015;Pata, Lord, & Lamb, 2014;Roller et al, 2018;Scherf, Guadagnin, Tier, & De Almeida Dias, 2019;Sofianidis, Dimitriou & Hatzitaki, 2017); dos para comprobar el impacto del método sobre la capacidad funcional de las mujeres (Bertoli, Biduski & Freitas, 2017;Vieira et al, 2017); tres artículos en los que se analizaron los efectos del Pilates sobre la composición corporal (Ruiz-Montero & Castillo-Rodriguez, 2018;Ruiz-Montero, Castillo-Rodríguez, Mikalacki, Nebojsa & Korovljev, 2014;Vasconcelos, Cardozo, Lucchetti & Lucchetti, 2016); ocho para determinar mejoras en el dolor corporal y la calidad de vida (Aibar-Almazan et al, 2019;Curi, Haas, Alves-Vilaca & Fernandes, 2018;de Oliveira, de Oliveira & Pires-Oliveira, 2015;Liposcki et al, 2019;…”
Section: Resultsunclassified
See 2 more Smart Citations
“…De los 41 artículos, encontramos nueve que emplean el método Pilates para la mejora de la fuerza muscular (Bergamin et al, 2015;Bertoli et al, 2018;Choi et al, 2019;de Carvalho, Mesquita, Pereira, Neto & Amaro Zangaro, 2017;de Oliveira, de Oliveira & Pires-Oliveira, 2018de Oliveira, Pires-Oliveira, Abucarub, de Oliveira & de Oliveira, 2017;Pinheiro et al, 2014); trece para mejorar el equilibrio y disminuir el riesgo de caídas (Aibar-Almazan et al, 2019;Barker et al, 2016;Bird & Fell, 2014;Cruz-Diaz et al, 2015;Gabizon, Press, Volkov, & Melzer, 2016;Irez, 2014;Josephs, Pratt, Calk Meadows, Thurmond, & Wagner, 2016;Markovic, Sarabon, Greblo & Krizanic, 2015;Mesquita, de Carvalho, Freire, Neto & Zangaro, 2015;Pata, Lord, & Lamb, 2014;Roller et al, 2018;Scherf, Guadagnin, Tier, & De Almeida Dias, 2019;Sofianidis, Dimitriou & Hatzitaki, 2017); dos para comprobar el impacto del método sobre la capacidad funcional de las mujeres (Bertoli, Biduski & Freitas, 2017;Vieira et al, 2017); tres artículos en los que se analizaron los efectos del Pilates sobre la composición corporal (Ruiz-Montero & Castillo-Rodriguez, 2018;Ruiz-Montero, Castillo-Rodríguez, Mikalacki, Nebojsa & Korovljev, 2014;Vasconcelos, Cardozo, Lucchetti & Lucchetti, 2016); ocho para determinar mejoras en el dolor corporal y la calidad de vida (Aibar-Almazan et al, 2019;Curi, Haas, Alves-Vilaca & Fernandes, 2018;de Oliveira, de Oliveira & Pires-Oliveira, 2015;Liposcki et al, 2019;…”
Section: Resultsunclassified
“…En cuanto al diseño, diez fueron estudios pre-post con un grupo de intervención (Bergamin et al, 2015;Bertoli et al, 2017Bertoli et al, , 2018Bird & Fell, 2014;Choi et al, 2019;Geremia, Iskiewicz, Marschner, Lehnen & Lehnen, 2015;Pata et al, 2014;Pérez et al, 2014;Pinheiro et al, 2014;Ruiz-Montero et al, 2014;Scherf et al, 2019) y seis pre-post con un grupo control y uno experimental de Carvalho et al, 2017;Irez, 2014;Ruiz-Montero & Castillo-Rodriguez, 2018;Sofianidis et al, 2017;Vasconcelos et al, 2016); cuatro ensayos clínicos aleatorizados (de Oliveira, Liposcki et al, 2019;Vieira et al, 2017); quince ensayos controlados aleatorizados (Aibar-Almazán et al, 2019;Aibar-Almazan et al, 2019;Barker et al, 2016;Cruz-Diaz et al, 2015;de Oliveira, de Oliveira & Pires-Oliveira, 2016;de Oliveira et al, 2018;Gabizon et al, 2016;Josephs et al, 2016;Markovic et al, 2015;Mesquita et al, 2015;Roller et al, 2018); dos estudios transversales (Ruiz-Montero et al, 2015) y un estudio piloto (Jurakic et al, 2017) (tabla 1).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Better body composition is normally associated with regular PE, thereby previous research observed differences in body composition between PE trained older women and non-trained older women [5,[19][20][21]. There even exist differences between active and inactive older women in body composition [22,23]. The PE trained older women's body composition improvements are produced in mid-thigh cross-sectional area [24], weight loss [23] fat mass and BMI [19], statistical significant and non-significant body weight, skeletal muscle mass and fat mass [5,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 94%
“…There even exist differences between active and inactive older women in body composition [22,23]. The PE trained older women's body composition improvements are produced in mid-thigh cross-sectional area [24], weight loss [23] fat mass and BMI [19], statistical significant and non-significant body weight, skeletal muscle mass and fat mass [5,[21][22][23][24][25]. Some of these studies are cross-sectional studies and others are RE interventions from 24 weeks to 24 months.…”
Section: Introductionmentioning
confidence: 99%